2011
DOI: 10.1016/j.yexcr.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal development and differentiation

Abstract: In this review, we present an overview of intestinal development and cellular differentiation of the intestinal epithelium. The review is separated into two sections: Section one summarizes organogenesis of the small and large intestines, including endoderm and gut tube formation in early embryogenesis, villus morphogenesis, and crypt formation. Section two reviews cell fate specification and differentiation of each cell type within the intestinal epithelium. Growth factor and transcriptional networks that reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
246
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(259 citation statements)
references
References 86 publications
5
246
0
8
Order By: Relevance
“…Consistent with these results, we measured by RT-qPCR a moderate but significant upregulation of the goblet cell marker Muc2 in NleVilcKO intestines, whereas ChromograninA and Lysozyme mRNA levels were unchanged ( Figure 3b). We found that the local increase in goblet cell number was preceded by the upregulation of Atoh1, a key regulator of secretory cell lineage commitment, 27 and of Spdef, which is required downstream of Atoh1 for goblet cell terminal maturation 28 (Figure 3c). Hes1 expression was unchanged, confirming that the absorptive lineage was not affected by Nle loss of function ( Figure 3c).…”
Section: Resultsmentioning
confidence: 91%
“…Consistent with these results, we measured by RT-qPCR a moderate but significant upregulation of the goblet cell marker Muc2 in NleVilcKO intestines, whereas ChromograninA and Lysozyme mRNA levels were unchanged ( Figure 3b). We found that the local increase in goblet cell number was preceded by the upregulation of Atoh1, a key regulator of secretory cell lineage commitment, 27 and of Spdef, which is required downstream of Atoh1 for goblet cell terminal maturation 28 (Figure 3c). Hes1 expression was unchanged, confirming that the absorptive lineage was not affected by Nle loss of function ( Figure 3c).…”
Section: Resultsmentioning
confidence: 91%
“…1, top). Epigenetic factors are of paramount importance throughout organogenesis, as endoderm-mesoderm interactions have been found to direct the formation of various surface patterns that characterize the adult epithelia [4]. During the first stage of morphogenesis, different rates of cell proliferation in the two layers give rise to residual stresses to promote a mechanical instability, which triggers the occurrence of regional specificities.…”
mentioning
confidence: 99%
“…Following induction and molecular modeling the endoderm undergoes folding in which the embryonic primary intestine forms. Although the process of endodermic tubulogenesis is still not thoroughly investigated, it is considered to include interaction with the mesenchyme which surrounds it [8]. The process is initiated by invagination in the anterior and posterior end of the embryo called anterior intestinal portal (AIP) and caudal intestinal portal (CIP).…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of embryogenesis, the gastrointestinal tract is a simple endoblastic tube covered by a layer of mesenchyme. Although the process of endoblastic tubulogenesis is not completely studied, it is presumed that it also includes interaction with the mesenchyme which surrounds it [8]. In mice this process ends on 9 th gestation day [9,10].…”
mentioning
confidence: 99%